THE PROBLEM OF IMPROVING DEFENSE TACTICS AND WAYS TO SOLUTION IN THE GAME OF VOLLEYBALL - Abadan Ismailova (Proximus Journal Publishing, 2024)
The article discusses the problem of improving defensive tactics in volleyball. Based on pedagogical observations of the competitive activities of highly qualified volleyball players, the team effectiveness of defensive actions was determined. Ways to solve the problem of optimizing defense tactics in the field are given.
Keywords: Volleyball; problem; attractiveness; attack